THE EFFECT OF VOCATIONAL GUIDANCE, JOB EXPECTATIONS, AND JOB APPRECIATION ON THE WORK READINESS OF STUDENTS OF VOCATIONAL SCHOOL OF FASHION IN YOGYAKARTA CITY - Ulfa, Ulfa; Widihastuti, Widihastuti (UNIVERSITAS PAKUAN, 2025)
This study aims to look at (1) the effect of vocational guidance on job readiness, (2) the effect of job expectations on job readiness, (3) the effect of job appreciation on job readiness, and (4) the effect of vocational guidance, job expectations, and work appreciation together on the job readiness of vocational high school (SMK) students in fashion in Yogyakarta City. This research is a quantitative research with a correlational approach. The subjects of this study were 248 students in grade XII of the fashion skills program from five vocational schools that have a fashion department in Yogyakarta City. A sample of 153 students was determined by simple random sampling technique, using the Slovin formula. Data collection was carried out using questionnaires. The content of the instrument was validated by expert judgement (validator of five expert lecturers) and Aikens V, and then the validity of the construct was carried out by the Confirmatory Factor Analysis test. Reliability estimation uses inter-rater and Alpha Cronbach reliability. Data analysis used multiple linear regression test, t test, and F test. (1) There was a positive and significant influence between vocational guidance on job readiness by 41.6%. (2) There is a positive and significant influence between job expectations on job readiness by 53.5%. (3) There was a positive and significant effect between work appreciation and job readiness by 58.5%. (4) Vocational guidance, job expectations, and work appreciation together have a positive and significant influence on the job readiness of fashion vocational school students in Yogyakarta City with a score of 71.1%. The remaining 28.9% was influenced by other variables outside of this regression equation or variables that were not studied in this study.